Occlusal Changes Following Posterior Tooth Loss in Adults. Part 3. A Study of Clinical Parameters Associated with the Presence of Occlusal Interferences Following Posterior Tooth Loss - Helen L. Craddock, PhD, M Dent Sci, BDS, MFDS, MRD, FDS (Rest Dent), RCS (Edin), (Journal of Prosthodontics, 2008)
Tooth positional changes following posterior tooth loss may alter arch forms and occlusal planes.